Long-term hospital resource utilization and associated costs of care for patients initiating nivolumab in advanced non-small cell lung cancer in France. (31st December 2022) - Grumberg, Valentine; Chouaïd, Christos; Cotté, François-Emery; Jouaneton, Baptiste; Jolivel, Ronan; Gaudin, Anne-Françoise; Reynaud, Dorothée; Assié, Jean-Baptiste; Borget, Isabelle
Abstract: Objectives: In advanced cancers, healthcare resource utilization (HCRU) and costs usually increase until death. However, few studies have measured HCRU over time in patients treated with immunotherapies. The objective was to describe the evolution of HCRU and costs over four years for patients with advanced non-small cell lung cancer (aNSCLC) initiating nivolumab. Materials and methods: Based on the French hospital reimbursement database, all aNSCLC patients initiating nivolumab in the 2nd line or later in 2015 or 2016 were followed until 2019. HCRU (including hospitalizations and hospital visits) and costs (payer perspective) were described annually after nivolumab initiation. Trends in HCRU were analyzed with the Mann-Kendall test. As most patients did not reach the four-year follow-up, cost-analysis was performed without adjustment throughout, without adjustment in uncensored cases only or with adjustment using for all patients using the Bang&Tsiatis method. Results: 10, 452 patients initiating nivolumab were evaluated. The percentage of patients hospitalized or with hospital visits decreased ( p  < .001) over the four-year follow-up with the exception of consultations. The number of hospital visits per patient decreased from 23.3 in Y1 to 13.2 in Y4 without adjustment and 18.3 with adjustment ( p  < .001). The overall hospitalization duration per patient (days) decreased from 36.0 (Y1) to 14.9 (Y4-unadjusted) and 20.5 (Y4-adjusted) ( p  < .001). Annual per capita costs also decreased. The method without adjustment provided the lowest cost over time (€44, 404 (Y1), €32, 206 (Y2); €28, 552 (Y3); €18, 841(Y4)) while the Bang&Tsiatis method presented the highest cost (€45, 002 (Y1), €36, 330 (Y2); €35, 080 (Y3); €28, 931 (Y4)). Conclusion: HCRU and costs for NSCLC patients treated with nivolumab decreased over time. Cost estimates are dependent on the statistical method used to take into account uncertainty, but costs decreased over time whatever the method used.